FICE SPECIAL TASK FORCE “HAND IN HAND”: IMPROVING SAFETY AND WELL-BEING FOR DISPLACED UKRAINIAN CHILDREN - Schneider, Alexander; Bilyk, Marianna; Moroz, Yelyzaveta (International Journal of Child, Youth and Family Studies, 2025)
FICE International is a network of professionals and organizations from over 30 countries that is committed to child and youth care. Its members work in social pedagogy, social work, psychology, and education to ensure high-quality support for children and young people. To assist vulnerable children during crises such as the war in Ukraine, FICE created the “Hand in Hand” task force in August 2022. Its mission is to improve safety and well-being for displaced children, especially those in alternative care. These children face trauma, loss, disrupted education, and mental health challenges, including acute stress and post-traumatic stress disorder. Hand in Hand provides vital social–emotional resources and ensures access to education and services, making a meaningful difference in the lives of crisis-affected children.